Genetic Association of the Antiviral Restriction Factor TRIM5α with Human Immunodeficiency Virus Type 1 Infection - Speelmon, Emily C.; Livingston-Rosanoff, Devon; Li, Shuying Sue; Vu, Quyen; Bui, John; Geraghty, Daniel E.; Zhao, Lue Ping; McElrath, M. Juliana (Journal of Virology, 2006)
Article Usage Stats Services JVI Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue Spotlights in the Current Issue JVI About JVI Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy JVI RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0022-538X Online ISSN: 1098-5514 Copyright © 2014 by the American Society for Microbiology. For an alternate route to JVI .asm.org, visit: JVI